Analisis Finansial Hasil Hutan Bukan Kayu Kemiri (Aleurites moluccanus) dan Asam (Tamarindus indica) (Studi Kasus Desa Sillu Kecamatan Fatuleu Kabupaten Kupang) - Corna Juliuster Marlin Selan; Mamie E. Pellondo’u; Nixon Rammang (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2023)
Non-timber Forest Products (NTFPs) Candlenut (Aleurites moluccanus) and Tamarind (Tamarindus indica) is one of the plants that has many benefits to support people's daily lives and also has a high value. Support people's daily lives and also have a fairly good selling value. In order to obtain an indicator of the sustainability of the business of the Forest Farmers Group, it is necessary to know its financial feasibility. It is necessary to know its financial feasibility. This research was conducted from March to April 2021 with the aim of analyzing the financial feasibility of Non-Timber Forest Products (NTFPs) Candlenut (Aleurites moluccanus) and Tamarind (Tamarindus indica) with interest rates. (Tamarindus indica) with interest rates and prices to determine whether business development is feasible or not. Whether the business development is feasible or not. Respondents in the study were Forest Farmers Group, the respondents were taken purposively, the methods used were observation and direct interview. Methods used were direct observation and interviews while the analysis of analysis used were Net Present Value (NPV), Benefit Cost Ratio (BCR) and Internal Rate of Return (IRR). Ratio (BCR) and Internal Rate Of Return (IRR). The results showed that Non-Timber Forest Products (NTFPs) Candlenut (Aleurites moluccanus) and Tamarind (Tamarindus indica). (Tamarindus indica) is feasible to develop because it has a value of the indicator with interest rates ≥ 10% are Candlenut (Aleurites moluccanus) with a value of 13% and Tamarind (Tamarindus indica) with 14%.